Analisis Risiko Kecelakaan Kerja Menggunakan Metode HIRADC Pada Gudang P.IV Divisi Gudang dan Pengantongan PT XYZ - Prashodang, Tryandika Rizkat; Nugraha, Isna (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Indonesia is a country that considers the agricultural sector as one of its economic drivers, with fertilizers being a vital material for agricultural activities. PT XYZ is a company engaged in fertilizer production with numerous fertilizer storage warehouses. The main activities in the warehouses include bagging and shipping out, which are not exempt from the risk of workplace accidents. These workplace accidents can be analyzed using the HIRADC method, which aims to identify hazards, assess risks, and implement appropriate risk control measures in Warehouse P. IV. The study concluded that there are six main activities and identified risks related to ergonomic, environmental, chemical, and physical factors. The results revealed that no hazards fell into the low-risk category, 15 hazards were categorized as medium risk, 5 hazards were categorized as high risk, and no hazards were classified as very high risk. In this study, the control efforts implemented focused on three aspects: engineering controls, administrative controls, and personal protective equipment (PPE).